Influence of Delta Ferrite Content on Corrosion Behavior of Austenitic Stainless Steel Nitronic 60 - Gigović-Gekić, Almaida; Bikić, Farzet; Avdušinović, Hasan (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2018)
Nitronic 60 (UNS S21800) is a highly alloyed austenitic stainless steel with increased content of manganese and silicon. It has a good mechanical and corrosion properties at elevated temperatures and loads. Nitronic 60 has the austenitic microstructure at room temperature but depending on chemical composition the presence of other phase in austenite matrix is possible, i.e. delta ferrite. The aim of this study is better understanding of delta ferrite content influence on corrosion sensitivity of Nitronic 60. The corrosion sensitivity test was conducted in the corrosion cell using potentiostat/galvanostat according to Standard ASTM G5 (Princeton Applied Research, model 263A-2, with the PowerCORR® software), (Standard, ASTM G5-94). Investigation was performed in 0.9% NaCl solution. Taffel extrapolation method was used to test general corrosion. Method of cyclic polarization was used for investigation of pitting corrosion. Tests were performed at room temperature, 20±1°C.The corrosion tests results indicate that the intensity of both examined forms of corrosion, general and pitting corrosion, is increased with increasing delta ferrite content.